Design Build a Smarthome Prototype on House Type 36 with IOT-Based Smartphone Control - Ultra Prayogi; Dahlan Abdullah (JINAV: Journal of Information and Visualization, 2022)
Technology's rapid development certainly benefits the people who use it. One example of technology today is the application of technology systems at home, with significant problems for homeowners, such as fire and theft. Incidents like this can result in losses for homeowners in terms of material and even to the point of causing loss of life. With such problems, it is necessary to have a system that can monitor these events. One solution to this problem is designing a smart home or smart home. The smart home or smart home is a term used to refer to a modern dwelling with remote control. The intelligent home prototype design for the type 36 house is an innovative home appliance design that uses automatic commands controlled by the homeowner's smartphone. This intelligent home prototype design research aims to be a reference for today's modern homes for the community, especially for type 36 houses. In this study, the five systems studied were automatic light control, automatic doors, gas leak detectors, fire smoke detectors, and room temperature detectors. Excess Commands from the prototype system are carried out using SMS from the GSM SIM900 module connected to the smartphone. The results of this study are an intelligent home prototype in a type 36 house that can be controlled via a smartphone. It is hoped that this automatic system device can make it easier for the community to carry out supervision at home to prevent unwanted things and help ease work so that people are more productive in carrying out other essential activities and provide a sense of security and comfort from danger in the house where they live. Beloved family.